Why ABM? : Policy issues in the missile defense controversy - Holst, Johan Jrgen, 1937-1994; Schneider, William, 1941-; Armbruster, Frank E. (Pergamon Press, 1969)
Why ABM?: Policy Issues in the Missile Defense Controversy focuses on the problems of invention and deployment of defenses against anti-ballistic missiles (ABM). The book first discusses early, present, and future missile defense systems, including the efficiency of missile defense and the use of missiles in penetration aids and tactics. The deployment of ballistic missile defense (BMD) is explained. The text takes a look at the missile defense systems of the Soviet Union and their participation in the arms race. The reactions of the Soviet Union on the use of BMD and positions of Soviets and.